In-vivo Ameliorative Potential Effect of N-Acetylcysteine and Gallic Acid against Hepatotoxicity Induced by Mercuric Chloride in Wistar Rats - Vanithasri , V.; Jagadeesan , G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Mercury is a highly toxic metal induces oxidative stress in the body and results in a variety of adverse health effects including liver damage. In the present experimental study was to investigate the hepatoprotective effect of some phytochemical on Mercury intoxicated rats. During treatment periods, a sub-lethal dose of mercuric chloride (1.29 mg/kg body weight) treated rat liver tissue shows hepatic injury is mainly associated with distortion of the metabolic function of the liver in rats, it is Hepatic damage can be evaluated by biochemical analysis of the serum tests, includes levels of serum Alanine and Aspartate aminotransferases, alkaline phosphatase, lactic dehydrogenase of liver marker enzymes. In the present experimental study, drastically altered in the level of Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline phosphatase (ALP), Lactic dehyrogenase (LDH) and Bilirubin levels were observed in the blood serum of mercuric chloride intoxicated Wistar rats. The activity of liver marker enzymes such as ALT AST, ALP and LDH were significantly increased. In addition, lipid peroxidation (LPO) were significantly increased while the activities of the levels of non enzymatic antioxidants (reduced glutathione (GSH)) and enzymatic antioxidants (glutathione peroxidase (GPx) superoxide dismutase (SOD) and catalase (CAT)) were significantly decreased in liver tissues and the toxicity with mercury is associated with oxidative stress in which mercury induces the formation of free radicals including ROS. It alters the antioxidant capacity of the cells to promote cellular damages. During the recovery period, the hepatic marker enzymes, enzymatic antioxidant and non-enzymatic antioxidant are restored to near normal level in liver tissues. Our experimental studies indicate that treatment for N-Acetylcysteine and Gallic acid exhibited the strong hepatoprotective activity against mercuric chloride induced liver damage in Wistar rat.